Experience of self-harm and its treatment in looked-after young people: an interpretative phenomenological analysis - Wadman, R.; Armstrong, M.; Clarke, D.; Harroe, C.; Majumder, P.; Sayal, K.; Vostanis, P.; Townsend, E. (Taylor & Francis, 2017)
Objectives: We report the first Interpretative Phenomenological Analysis examination of self-harm and experience of clinical services in young people in the public care system. Methods: Qualitative interviews with 24 looked-after young people. Results: Prevalent themes were 1) Changes in care placement, 2) Feelings of anger, 3) Not wanting/feeling able to talk, 4) Developing coping techniques, 5) Clinical services: A relational mixed bag (subthemes: feeling (i) patronised, not listened to, (ii) nothing being done, (iii) comfortable/able to talk). Conclusions: Placement change and anger were highly salient to self-harm in this group and experiences of clinical services depended on individual relationships with clinicians. Implications include increasing compassion in therapeutic relationships, recognizing and managing emotional dysregulation and increasing support during placement changes.